PENGARUH SISTEM TANAM LEGOWO DAN PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PADI LOKAL ACEH AKSESI SIGUPAI - Chairudin, Chairudin; Setyowati, Mita; Hussaleh, Taufiq (Jurnal Agrotek Lestari, 2016)
The potential to increase rice production can be improved through the application of new innovation, one of them using the system Legowo row planting and use of organic fertilizers. This study aims to determine the effect of planting system legowo and organic fertilizers on the growth and production of local rice crops Aceh Accession real Sigupai and whether the interaction of both factors. This study uses split plot design, with three replications, where subplots nested within the main plot. Subplot consisted of three (3) the standard treatment Legowo planting system (S), namely: S1 = Cropping systems Legowo 2: 1, S2 = System Legowo planting 3: 1, S3 = Cropping systems Legowo 4: 1. While the main plot consists of three (3) the standard treatment of organic fertilizers (P) ie: P1 = 5 ton ha -1, P2 = 10 ton ha -1, P3 = 15 ton ha -1. The results showed that planting system legowo not affect the growth of the rice plant, but affect the results of rice. The highest yield obtained in planting system Legowo 4: 1 and legowo 2: 1 which is significantly different from the System Legowo 3: 1. Organic fertilizer had no effect on the growth and yield of rice plants. There is no interaction between legowo cropping system and organic manure on the yield of rice plants. Keywords: legowo cropping system, local accession aceh, organic fertilizer, production